Analisis Kelayakan Buku Siswa Kelas IV Tema Makhluk Hidup Kurikulum 2013: Feasibility Analysis of Class IV Student Books on the Theme of Living Creatures 2013 Curriculum - Amalia, Delora Jantung (Pedagogia : Jurnal Pendidikan, 2017)
The purpose of education in Indonesia is to educate the life of the nation which has been presented in the preamble of the 1945 Constitution to educate the nation to achieve the goal of education, the national development in the field of education as a whole, continuous and sustainable. Development in the field of education is one effort to improve the quality of the nation. A quality nation is a nation that will advance education. In the curriculum of 2013, the learning which initially embraces the learning of subject matter becomes thematic learning. The approach used in this study is a qualitative approach, which in the qualitative approach can generate descriptive data in the form of written words or oral form of someone. Qualitative approach used in this research because in this research analyze a book. The results of the discussion in this study are: In the spiritual dimension is 45.00% in the category less feasible because many activities are less emphasis on sentences that contain spiritual elements. In this spiritual usnur free from the elements of SARA, pornography. On the social dimension is considered very high displays social aspects that reach 100% very feasible, almost every activity. In the percentage of knowledge dimensions obtained 87.5% is very feasible for use by students and the 83% skills dimension is very reasonable in terms of reasoning, problem solving.